SOSIALISASI DAN PEMBUATAN NUGGET DARI AMPAS TAHU UNTUK MENINGKATKAN EKONOMI MASYARAKAT DI KAMPUNG CEMPAKA PUTIH DESA ANYAR – BANTEN - Hidayah, Alma Nurul; Listiawati, Listiawati; Fadillah, Rizky Imam; Suneni, Suneni; Indah, Siti (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2022)
The current management of the tofu industrial waste in SMEs has not been managed properly, the solid and liquid waste is discharged into the environment, such as ditches and rivers. For this reason, it is necessary to increase efforts to utilize the waste generated by community activities. The effort to utilize this waste is not only a form of environmental management that is inherent in the quality of human life, it is also an effort to develop human resources that can open up new business opportunities. Many types of waste can be reused through recycling or converted to other useful products, one of which is waste. from the tofu industry. The waste usually still contains fiber, carbohydrates, protein, fat, organic acids, and minerals and basically can undergo biological changes so that it can be converted to other products such as energy, food, feed, organic fertilizers and others. In an effort to build small and medium-sized enterprises (SMEs), first of all the chemical and physical properties must be known, so that various possible products can be estimated. Then the selected product is considered with its market and techno-economy. For example, tofu dregs have chemical properties that are dominated by protein so that they can be processed into food such as nuggets which function as a source of protein and can improve the community's economy